2009
DOI: 10.1007/s12022-009-9066-2
|View full text |Cite
|
Sign up to set email alerts
|

Paraganglioma of the Thyroid Gland: A Rare Entity

Abstract: Paragangliomas are neuroendocrine tumors. The thyroid gland is one of the anatomic sites in which paraganglia are not normally located and are exceptionally rare. We report a case of a 36-year-old Hispanic woman with a soft mass measuring about 30 mm in the right thyroid lobe. Patient was operated on and the neoplasm showed microscopically a typical nesting organoid pattern (zellballen). The inmunohistochemical analysis revealed that the tumor showed strongly and diffuse stain for NSE, Synaptophysin, Chromogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Thyroid paraganglioma is a rare entity with approximately 60 cases that are reported, including our series (LaGuette et al 1997, Yano et al 2007, Ferri et al 2009, González Poggioli et al 2009, Basu & Viswanathan 2011, Phitayakorn et al 2011, Varsavsky et al 2011, Armstrong et al 2012, Capel 2012, Castelblanco et al 2012, Costinean et al 2012, Evankovich et al 2012, Kieu et al 2012, Mohyuddin et al 2013, Yu et al 2013. A major question is whether the rare entity of thyroid paraganglioma is of practical clinical relevance.…”
Section: Discussionmentioning
confidence: 74%
“…Thyroid paraganglioma is a rare entity with approximately 60 cases that are reported, including our series (LaGuette et al 1997, Yano et al 2007, Ferri et al 2009, González Poggioli et al 2009, Basu & Viswanathan 2011, Phitayakorn et al 2011, Varsavsky et al 2011, Armstrong et al 2012, Capel 2012, Castelblanco et al 2012, Costinean et al 2012, Evankovich et al 2012, Kieu et al 2012, Mohyuddin et al 2013, Yu et al 2013. A major question is whether the rare entity of thyroid paraganglioma is of practical clinical relevance.…”
Section: Discussionmentioning
confidence: 74%
“…We describe a patient with a newly discovered SDHD mutation who first presented with an asymptomatic parapharyngeal mass and subsequently was found to have a cervical sympathetic PGL. PGLs of the head and neck have been detected in nearly 20 distinct sites 1, 2, 20. However, they are usually seen in 3 locations: the carotid body at the common carotid artery bifurcation, the jugular foramen, and the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, parasympathetic PGLs develop in the head and neck region and sympathetic PGLs derive from sympathetic tissue in the abdominal or thoracic locations. In the head and neck, parasympathetic PGLs occur at highly predictable sites, and the carotid body has been cited as the most common site of occurrence, followed in frequency by the middle ear, jugular foramen, vagus nerve, larynx, pharynx, the ciliary ganglion of the orbit, or the thyroid gland 1, 2. On the other hand, head and neck sympathetic PGLs are exceedingly rare, with no more than 10 cases reported in the literature to date 3–8…”
mentioning
confidence: 99%
“…A comprehensive search of PubMed showed that only 38 cases had been reported in the English literature since 1974. 127 However, no case contained melanin. Pigmentary paraganglioma is a special type of paraganglioma that usually occurs in the uterus, 28 orbit, 29 heart, 30 urinary bladder, 31 and temporal horn, 32 with reported cases also in the mediastinum, lumbar spine, retroperitoneum, and others.…”
Section: Introductionmentioning
confidence: 92%